Iranian Foreign Policy during Ahmadinejad - Warnaar, Maaike. author. aut Link
XII, 292 p.
Keywords: Written for scholars and practitioners puzzled by Iran's foreign policy choices, this book argues that Iran's foreign policy behavior is best understood in the context of the regime's foreign policy ideology, which is rooted in a conception of Iran as a nation changed by the 1979 Revolution and an example to other nations in a changing world.